A COVID-19 Pandemic Sustainable Educational Innovation Management Proposal Framework - Scavarda, Annibal; Dias, Ana; Reis, Augusto; Silveira, Haydee; Santos, Isabel (Sustainability, 2021)
The COVID-19 pandemic has promoted a big change in the educational sector. Suddenly, teachers, professors, and students had to migrate from presential classes to the online system without prior notice or a training course. This paper aimed to verify how the need of a rapid change to the online system in response to the impossibility of keeping the presential system due to the mandatory social distancing imposed by the COVID-19 pandemic has affected relationships and performance of teachers, professors, and students, as well as review the technologies and procedures adopted by them to innovate and achieve sustainable education. To address the empirical side of this exploratory research, the authors of this paper sent an email questionnaire to kindergarten, elementary and high school teachers in the City of Rio de Janeiro (Brazil), as well as to professors of the top 197 Brazilian universities. To address theoretical side of this exploratory research, an investigation was carried out through scientific databases. The data were analyzed with SPSS (Statistical Package for the Social Sciences), version 22.0, and with Microsoft Excel 2007. As a result, this paper showed that social isolation and transition to the online system greatly affected the work conditions of teachers and professors, as well as the learning process of students. Anyway, sustainable actions were taken to overcome these challenges. Furthermore, this paper proposed a framework that might support the development of new studies, filling the literature gap on the subject.